PENGARUH MOTIVASI TERHADAP PERILAKU KERJA PETANI BAWANG MERAH DI DESA NALUI KECAMATAN JARO KABUPATEN TABALONG - Purna Kusumayana (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2018)
This research is aimed to find out the influence of motivation on the working behavior of red onion farmers, knowing the dominant motivation of red onion farmer in Nalui Village District of Jaro Tabalong Regency. Method of reserch used with data collected using interviews. Data collection was conducted from May to August. Analysis tool used the qualitative analysis about working behavior of rubber farmer, motivation of power, motivation of afiliation, motivasi of achievement. Quantitative analysis uses multiple regression analysis with simultaneous testing, partial testing, correlation coefficient and coefficient of determination using sofware SPSS 23 for windows. The result of reserch shows that motivation not give influence to the working behavior of red onion farmer with value Fcount 2,335 smaller than Ftable 3.59. Motivational variables such as power motivation, affiliation motivation, and achievement motivation are not motivated to the working behavior of onion farmers in Nalui Village District of Jaro Tabalong Regency.